Literature Review: Peran Strategi Akuisisi terhadap Pertumbuhan dan Keunggulan Kompetitif Perusahaan Multinasional Studi Kasus pada PT Bank Maybank - Sarmawati; Ravi Nursetiadi; Muhammad Riski; Robert Tua Barasa (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Acquisition strategy is one of the main approaches used by multinational companies to accelerate growth and strengthen their competitive position in the global market. This study aims to systematically examine the role of acquisition strategy in driving corporate growth and creating sustainable competitive advantage. The method used is a literature review by analyzing various relevant scientific sources in the recent period that discuss acquisitions, international expansion, and global business strategy. The results of the study indicate that acquisitions can provide rapid access to strategic resources, such as technology, new markets, and organizational capabilities, which are difficult to obtain through organic growth. In addition, this strategy has been proven to improve operational efficiency, expand market share, and strengthen the company's bargaining position in global competition. However, the success of an acquisition is greatly influenced by post-acquisition integrity factors, organizational cultural fit, and managerial ability to manage change. Thus, an acquisition strategy functions not only as an expansion tool, but also as a strategic mechanism to create added value and long-term competitive advantage for multinational companies. Therefore, multinational companies need to carefully design and manage their acquisition strategies to maximize benefits and minimize potential risks.